Pelaksanaan Sanra Galung Perspektif Ekonomi Islam - Mardatillah Mardatillah; Zaenab Zaenab; Nashrurrahman Nashrurrahman; Husni Nasir (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2022)
This research was conducted to know: (1) the implementation of sanra galung by the rice farming community of Wadilmuqaddas hamlet, Lawatu Ea village, Kec. North Poleang, Kab. Bombana; (2) an Islamic economic review of the implementation of sanra galung by the rice farming community of Wadilmuqaddas hamlet, Lawatu Ea village, Kec. North Poelang, Kab. Bombana. This research is field research with a qualitative approach method, sourced from primary data and secondary data. The researcher acts as the main instrument in this research by collecting and assessing the quality of the data and the validity of the information obtained from the results of observations, interviews, and documentation activities. The data is processed based on analytical procedures that are natural settings with a phenomenological and sociological approach through three stages, namely data reduction, data display, and conclusions. The results of this study indicate that: (1) the implementation of sanra galung by the people of Wadilmuqaddas hamlet, Lawatu Ea village, North Poleang sub-district is carried out according to customs such as not involving witnesses, without a letter of agreement and the use of collateral by the massanra (debtor) which in the broad sense of the community has not to understand the provisions of Islamic law. (2) the implementation of sanra galung in the hamlet of Wadilmuqaddas based on an Islamic economic review is not by the law or Islamic economic principles.